Cross-sectional and longitudinal comparison of health-related quality of life and mental well-being between persons with and without post COVID-19 condition - Scott, Emily Stella; Lubetkin, Erica I.; Janssen, Mathieu F.; Yfantopolous, John; Bonsel, Gouke J.; Haagsma, Juanita A. (Frontiers in Epidemiology, 2023)
Background: Still little is known about the impact of post COVID-19 condition (PC) on health-related quality of life (HRQOL) and mental well-being. We compared participants with PC with three groups: an acute COVID-19 infection (AC) only, at least one chronic condition (CC) but no COVID-19, or no condition at all, healthy (PH). Between these disease groups, we also estimated and compared HRQOL and mental well-being change over time. Methods: Participants from six countries (Greece, Italy, Netherlands, Sweden, United Kingdom and United States) completed two web-based questionnaires (T1=April-May 2020 and T2=April-June 2022). Primary outcomes were HRQOL, measured by EQ-5D-5L and EQ VAS, and mental well-being (measured by World Health Organisation-Five (WHO-5) Well-Being Index, Patient Health Questionnaire (PHQ)-9 and General Anxiety Disorder (GAD)-7). All analyses were stratified by the disease groups. Results: In total, 4999 participants filled out both surveys: 240 were in PC, 107 in AC, 1798 in CC and 2854 in PH. At T2, the mean EQ-5D-5L index values for the PC, AC, CC and PH groups were 0.70, 0.73, 0.75 and 0.92 (p<.001), respectively. Mean EQ VAS scores were 66, 65, 68 and 81 (p<.001), respectively. Poor mental well-being, depression and anxiety mean values were highest in the PC group (47.7; 9.1; 7.4), followed by the AC group (51.1; 7.7; 5.7), CC group (56.1; 5.2; 4.2) and the PH group (65.6; 2.8; 2.5), respectively (p<.001 between groups). Over time, HRQOL deteriorated in all groups, apart from the PH group. We observed the largest deterioration in the CC (EQ-5D-5L index: Δ0.03, p<.001) and AC group (EQ VAS: Δ6.3, p<.001). For the mental well-being outcomes, deterioration for WHO-5 and PHQ-9 were largest in the AC group (Δ4.8, p=.016; Δ-1.3, p=.012). Rates for GAD-7 improved for the PH and CC groups (PH: Δ1.27, CC: Δ0.56, p<.001). Conclusions: In the cross-sectional analysis, participants with PC had the worst HRQOL and mental well-being compared to the other groups. In terms of change since the start of the COVID-19 pandemic, HRQOL and mental well-being deterioration was highest among AC participants and had a lower impact among PC participants, most likely due to pre-existing chronic disease.